Causes of Corruption, Socio-Political Consequences - Uzokov Botir; Khidirov Khoshim Ibodullaevich (Genius Journals, 2022)
This article discusses the causes of corruption, it’s socio-political aspects, consequences, the fact that corruption is a negative phenomenon in the criminal society, which requires the establishment of special control measures of the state, it’s changeability, politically correction and informative.
Keywords: Corruption; UN; Council of Europe; European Union